Gender employment practices amongst small and medium scale enterprises: A comparitive study of different industries in Gauteng - Onukogu, Chioma (My University, 2006)
The study investigated gender employment practices and conditions of work among small and medium scale enterprises (SMEs) in Gauteng Province of South Africa. A comparison of the practices and conditions between productive and service industries is clearly the major focus of the research. Interviews were conducted on two productive and two service industries (all private) situated in Benoni and Johannesburg respectively. The research found that generally, SMEs, in the productive and the service sectors contribute to job creation. Evidence shows that women are going into previously male dominated jobs like electrical and mechanical jobs, but the movement is quite minimal. This is a sign of progress on the part of women and a shift from the traditional belief that certain jobs are exclusively meant for men. The study found a salient discrepancy between the rhetoric of gender equality and the practice of gender equality in all the industries. There are clear signs that the legislation on minimum conditions of employment is followed in the productive industries than in the service industries but both still stick to the traditional gender division of labour.
Student Number: 0304476F Faculty of Humanities Maters in Arts
Keywords: Gender; Employment; Small, Medium Enterprises; Productive Industries; Service Industries; SMEs; Job Creation; Gender division labour; Gender equality